Upaya Meningkatkan Hasil Belajar Passing Atas dalam Pembelajaran Bolavoli Menggunakan Media Bola Gantung - Ana Abadi, Resky (IKIP PGRI Pontianak, 2023)
This study was aimed to improve the learning outcomes of class VII students at MTs Al Ulum Puuwatu Kendari on the subject of upper passing in volleyball games using hanging balls as media. The research method used in this study was Classroom Action Research (CAR). The study was carried out in 3 cycles, each cycle consisting of 2 meetings, namely planning, action, observation and reflection. The subject of this research was conducted in class VII students of MTs Al – Ulum. The total sample was 29 students. The data collection techniques used in this study were test methods, observation methods and documentation. After the researcher conducted classroom action research, it can be concluded that there was an improvement in student learning outcomes in Physical Education subjects. The learning outcomes of students on the initial test (pretest) were 61.73, after being treated in cycle I the average score of students increased to 64.34 with a completeness percentage of 20.69%. In cycle II the average score of students was 70.52 with a success percentage of 58.62%. In cycle III the average score of students was 77.69 with a success percentage of 86.21%. This finding showed an improvement in student learning outcomes after the implementation of hanging ball media.